2013
DOI: 10.1371/journal.pone.0072186
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Polymorphism in TOX3 Is Associated with Survival of Gastric Cancer in a Chinese Population

Abstract: PurposeRecently, genetic polymorphism (rs3803662C>T) in TOX3 was reported to induce the risk of breast cancer. In this study, we hypothesized that rs3803662 could influence gastric cancer survival outcomes.MethodsWith multiplex SNaPshot method, we genotyped TOX3 rs3803662 in 880 gastric patients with surgical resection. The association between genotype and survival outcomes was performed by the Kaplan-Meier method, Cox regression analysis models and the log-rank test.ResultsThere was no association in the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Dittmer et al observed that overexpression of TOX3 protects neuronal cells from cell death by inducting anti-apoptotic transcripts and inhibiting pro-apoptotic transcripts; it depends on the phosphorylated CREB or CITED1 within the transcriptionally active complex interacting with the native CREB and inducing the CREB-responsive BCL-2 promoter ( 18 ). Furthermore, there are certain studies demonstrating that TOX3 is correlated with other carcinomas ( 19 21 ). A study by Birkenkamp-Demtroder et al revealed that TOX3 overexpression in bladder cancer cells reduces cell proliferation and affects the interferon signaling pathway ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dittmer et al observed that overexpression of TOX3 protects neuronal cells from cell death by inducting anti-apoptotic transcripts and inhibiting pro-apoptotic transcripts; it depends on the phosphorylated CREB or CITED1 within the transcriptionally active complex interacting with the native CREB and inducing the CREB-responsive BCL-2 promoter ( 18 ). Furthermore, there are certain studies demonstrating that TOX3 is correlated with other carcinomas ( 19 21 ). A study by Birkenkamp-Demtroder et al revealed that TOX3 overexpression in bladder cancer cells reduces cell proliferation and affects the interferon signaling pathway ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taking together, these findings could help to understand the mechanism of action of TOX in CTCL and provide clues to novel therapeutics for CTCL. Several strategies have been employed to enhance the efficacy of current treatments and to find new therapeutic options to improve survival and quality of life for patients with SS and other forms of advanced CTCL [19,20,30]. TOX encodes a high-mobility group family (HMG) domain binding nuclear protein which regulates the differentiation of developing T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the efficacy of 5-Fu is positively associated with its action duration (Hu et al, 2013;Yoney et al, 2013). In general, the release time of 5-Fu wrapped with adjuvant is not more than 1 day, whereas that of sustained-release 5-Fu implantation is more than 10 days, which overcomes the disadvantage of conventional chemotherapeutic drugs with short action duration Zhang et al, 2013) . Such preparations can also be easily placed at any site of residual tumours during surgery and stably maintain a higher drug concentrations at the administered area for a long time, being conductive to killing the residual tumours not removed during surgery, micrometastases and intraperitoneal free cancer cells.…”
Section: Discussionmentioning
confidence: 99%